Practical internal and external cooling methods do not influence rapid recovery from simulated taekwondo performance - Pariyavuth P. (2023)
Background/Objectives: The influence of post-exercise cooling on recovery has gained much attention in the empirical literature, however, data is limited in regards to optimizing recovery from taekwondo performance when combat is repeated in quick succession within the same day. The aim of this study was therefore to compare the effects of external and internal cooling after simulated taekwondo combat upon intestinal temperature (Tint), psychomotor skills (reaction time, response time, movement time), and neuromuscular function (peak torque, average power, time to reach peak torque). Methods: Using a randomized counterbalanced crossover design, 10 well-trained male taekwondo athletes completed four recovery methods on separate occasions: passive recovery (CON), a 5-minute thermoneutral water immersion (35°C) (TWI), a 5-min cold water immersion (15°C) (CWI), and ice slurry ingestion (-1°C) (ICE; consumed every 5 min for 30 min). Heart rate (HR), blood lactate (Blac) concentrations, and Tint were determined at rest, immediately after combat, and at selected intervals during a 90-min recovery period. Neuromuscular functional (measured with isokinetic dynamometer) and psychomotor indices were assessed at baseline and after the recovery period. Results: ICE led to a significantly lower Tint at 30 min (P<0.01) and 45 min (P<0.01) after simulated combat; 15-30 min after cessation of ingesting ice slurry, compared with the CON and TWI conditions, respectively. However, there were no differences in Tint across time points between the other conditions (P>0.05). Psychomotor skills and neuromuscular function indices returned to baseline values after the 90 min recovery period (P>0.05) with no differences observed between conditions (P>0.05). Conclusion: The present findings suggest that internal (ICE) and external (CWI) recovery methods appear to have little impact on physiological and functional indices over the time course required to influence repeated taekwondo combat performance.